2016
DOI: 10.1021/acsami.5b11152
|View full text |Cite
|
Sign up to set email alerts
|

Epichlorohydrin-Cross-linked Hydroxyethyl Cellulose/Soy Protein Isolate Composite Films as Biocompatible and Biodegradable Implants for Tissue Engineering

Abstract: A series of epichlorohydrin-cross-linked hydroxyethyl cellulose/soy protein isolate composite films (EHSF) was fabricated from hydroxyethyl cellulose (HEC) and soy protein isolate (SPI) using a process involving blending, cross-linking, solution casting, and evaporation. The films were characterized with FTIR, solid-state (13)C NMR, UV-vis spectroscopy, and mechanical testing. The results indicated that cross-linking interactions occurred in the inter- and intramolecules of HEC and SPI during the fabrication p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
85
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(95 citation statements)
references
References 48 publications
9
85
1
Order By: Relevance
“…The typical polysaccharides are alginate, hyaluronic acid (HA), agarose, chitosan, dextran, cellulose, pectin, gellan, and heparin . Polysaccharides with fast gelation properties are appropriate for the fabrication of complex 3D scaffolds with various morphologies, such as microfibers, microspheres, membranes, and defined blocks, thus providing architectural cues for tissue/organ constructs in vitro. The natural proteins used as cell culture matrices are collagen, gelatin, fibrin, silk protein (mainly referring to silk fibroin), poly‐ l ‐lysine (PLL), and soy protein .…”
Section: Snapshot Of Hydrogelsmentioning
confidence: 99%
“…The typical polysaccharides are alginate, hyaluronic acid (HA), agarose, chitosan, dextran, cellulose, pectin, gellan, and heparin . Polysaccharides with fast gelation properties are appropriate for the fabrication of complex 3D scaffolds with various morphologies, such as microfibers, microspheres, membranes, and defined blocks, thus providing architectural cues for tissue/organ constructs in vitro. The natural proteins used as cell culture matrices are collagen, gelatin, fibrin, silk protein (mainly referring to silk fibroin), poly‐ l ‐lysine (PLL), and soy protein .…”
Section: Snapshot Of Hydrogelsmentioning
confidence: 99%
“…The incorporated PU elastomer blue‐shifts the peak of SP at 1644–1650 cm −1 in the SP‐PU, as the newly formed intermolecular hydrogen bonds between the SP and PU partly break the intramolecular hydrogen bonds within the SP matrix . In addition, it is observed that a new peak appears at 1106 cm −1 , and the absorption intensities of the peaks around 1391 (COO bending) and 1446 cm −1 (NH blending) also increase, which all indicate that the PU induces crosslinking reactions and forms multiple hydrogen bonds with the SP molecules thus influencing the chemical environment of the SP functional groups . After incorporating the D‐PU elastomer, the intensity of the peaks at 1515, 1645, and 3278 cm −1 decrease, which is mainly because that the catechol OH of D‐PU further forms strong physical intermolecular interactions with the OH and amide groups of the SP molecules .…”
Section: Resultsmentioning
confidence: 93%
“…After incorporating the D‐PU elastomer, the intensity of the peaks at 1515, 1645, and 3278 cm −1 decrease, which is mainly because that the catechol OH of D‐PU further forms strong physical intermolecular interactions with the OH and amide groups of the SP molecules . Moreover, another new characteristic peak appears at 1370 cm −1 (CN stretching) in the SP‐D‐PU spectra, evidently demonstrating that the catechol of D‐PU induces the PU to further react with the SP matrix by means of Schiff base reactions …”
Section: Resultsmentioning
confidence: 94%
“…With an increase of worldwide environmental pollution caused by nonbiodegradable polymers and the impact of growing petroleum crisis, the research and development of biodegradable materials from renewable resources, including cellulose, starch, lignin, chitin, chitosan, vegetable oil, and protein have attracted much attention. Among those natural products, soy oil might be the most suitable one to be used in synthesizing polymers, especially polyurethane, because of its good solubility, excellent miscibility, low cost, high output, and easy to modify.…”
Section: Introductionmentioning
confidence: 99%